x/5=y/3 x/7=z/3 2x-y-z=34
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 12:09:04
x/5=y/3x/7=z/32x-y-z=34x/5=y/3x/7=z/32x-y-z=34x/5=y/3x/7=z/32x-y-z=34由已知得3x=5y=7zy=3/5xz=3/7x将一直带入2x
x/5=y/3 x/7=z/3 2x-y-z=34
x/5=y/3 x/7=z/3 2x-y-z=34
x/5=y/3 x/7=z/3 2x-y-z=34
由已知得3x=5y=7z y=3/5x z=3/7x
将一直带入2x-y-z=34中
2x-3/5x-3/7x=34
解得x=35 y=21 z=15
x/5=y/3=t
x=5t,y=3t
x/7=z/3
z=(3/7)x=(15/7)t
2x-y-z=34
10t-3t-(15/7)t=34
(49-15)t=34*7
t=238/34
=7
x=5t=35,y=3t=21,z=(15/7)t=15
x+y-z=3 y+z-x=5 z+x-y=7 求x,y,z
x/2=y/3=z/5 x+3y-z/x-3y+z
若X:Y:Z=5:6:7那么(Y-X):(Y+Z)和(X+2Y+3Z):(3X+2Y+Z)
已知(x+y)(x+z)=x,(y+z)(y+x)=2y,(z+x)(z+y)=3z,求x,y,z
试证明(x+y-2z)+(y+z-2x)+(z+x-2y)=3(x+y-2z)(y+z-2x)(z+x-2y)
已知x-y/x+y=y+z/2(y-z)=z+x/3(z-x),求证8x+9y+5z=0THX..
(4x-2y-z)-{5x-[8y-2z-(x-2y)]-x-(3y-10z)}=?
x+Y+Z=1 X+3Y+7Z=-1 X+5Y+8Z=2x+Y+Z=1X+3Y+7Z=-1X+5Y+8Z=2
{5x-3y+z=2{5x+2y-4z=3{-5x+y-z=2 {x-y-z=-1{3x+5y+7z{4x-y+2x=-1
x/5=y/3 x/7=z/3 2x-y-z=34
3x-y=-7,y+2z=2,2x-2z=-5 求x,y,z
x+y+z=0,3x-2y-2z=5,y-z=2x-7
X-Y-Z=0 X+Y-3Z=4 2X-5Y+7Z=21
2x+5y+4z=6,3x+y-7z=-4,x+y-z=?
3x+7y+4z=35,x+5y+2z=40,x+y+z=( )
{x+y+z=1 {x+3y+7z=-1 {x+5y+8z=2
{x+y+z=1 {x+3y+7z=2 {x+5y+19z=4
1.{x:y:z=3:4:5 2x+3y-5z=-142.{x-y-z=-1 3x+5y+7z=11 4x-y+2z=-13.{x+y=1 x+z=0 2x+y+2z=44.{x-y+z=-3 2x-y-z=-2 -3x+y+z=-15.{x-y+z=-3 3x+y-4z=6 2x+y-z=36.{x-2y+5z=16 2x+y-5z=7 2x-y+z=38